(untitled) (Colombia Medica, 2024)
Background: Differences in asthma prevalence between urban and rural areas have been observed worldwide. Epidemiological studies in middle- and low-income countries suggest that internal migration processes may partly explain these disparities. Objective: To investigate the association between internal migration and asthma in children living in transitional areas of Ecuador. Methods: A cross-sectional study was conducted using data from a birth cohort of children living in a tropical coastal region in northwestern Ecuador. Asthma indicators included wheezing in the past 12 months, ever wheezing, and asthma diagnosis by a doctor. Internal migration was defined as a change of residence between geographical units: cantonal, parish, and census tract. The relationship between asthma and migration was analyzed using binary logistic regression. Results: Of 2404 participants, 1818 children met the inclusion criteria. Among them, 2.8% experienced cantonal migration, 11.9% parish migration, and 24.6% census tract migration. The prevalence of wheezing in the past 12 months, ever wheezing, and asthma diagnosis by a doctor was 13.1%, 33.3%, and 7%, respectively. Children with a history of cantonal migration were more likely to have experienced wheezing compared to those who did not migrate (OR 1.56; 95%CI 0.87–2.79). Conclusions: Changes in residence between smaller or adjacent geographic units appeared not to be associated with asthma prevalence. However, cantonal migration may play a role in respiratory health outcomes.